Axillary Ultrasound Identifies Residual Nodal Disease After Chemotherapy: Results From the American College of Surgeons Oncology Group Z1071 Trial (Alliance) - Le-Petross, Huong T.; McCall, Linda M.; Hunt, Kelly K.; Mittendorf, Elizabeth A.; Ahrendt, Gretchen M.; Wilke, Lee G.; Ballman, Karla V.; Boughey, Judy C. (American journal of roentgenology (1976), 2018)
The purpose of this study is to determine lymph node features on axillary ultrasound (US) images obtained after neoadjuvant chemotherapy that are associated with residual nodal disease in patients with initial biopsy-proven node-positive breast cancer. All patients had axillary US performed after neoadjuvant chemotherapy. Axillary US images were centrally reviewed for lymph node size, cortical thickness, and cortical morphologic findings (type I indicated no visible cortex; type II, a hypoechoic cortex ≤ 3 mm; type III, a hypoechoic cortex > 3 mm; type IV, a generalized lobulated hypoechoic cortex; type V, focal hypoechoic cortical lobulation; and type VI, a totally hypoechoic node with no hilum). Lymph node characteristics were compared with final surgical pathologic findings. Axillary US images obtained after neoadjuvant chemotherapy and surgical pathologic findings were available for 611 patients. Residual nodal disease was present in 373 patients (61.0%), and 238 (39.0%) had a complete nodal pathologic response. Increased cortical thickness (mean, 3.5 mm for node-positive disease vs 2.5 mm for node-negative disease) was associated with residual nodal disease. Lymph node short-axis and long-axis diameters were significantly associated with pathologic findings. Patients with nodal morphologic type I or II had the lowest rate of residual nodal disease (51 of 91 patients [56.0%] and 138 of 246 patients (56.1%), respectively), whereas those with nodal morphologic type VI had the highest rate (44 of 55 patients [80.0%]) (p = 0.004). The presence of fatty hilum was significantly associated with node-negative disease (p = 0.0013). Axillary US performed after neoadjuvant chemotherapy is useful for nodal response assessment, with longer short-axis diameter, longer long-axis diameter, increased cortical thickness, and absence of fatty hilum significantly associated with residual nodal disease after neoadjuvant chemotherapy.